Formulation of Ethanolic Extract of Guava Fruit Flesh (Psidium guajava L.) as a Lip Moisturizer - Yoli Anathasia; Suryanto; Sudewi; Sumardi (Yayasan Penelitian dan Inovasi Sumatera, 2023)
Background: Guava fruit (Psidium guajava L.) is known for its antioxidant properties, attributed to its content of beta carotene and phenolic compounds such as quercetin, guavin, protocatechuic acid, ferulic acid, gallic acid, caffeic acid, and vitamin C. However, the use of guava fruit flesh in lip balm formulations has not been extensively studied. Objective: This research aims to determine whether the ethanolic extract of guava fruit flesh can be formulated into a lip balm preparation that provides moisture at certain concentrations without irritating the lip skin. Method: This study utilized the guava fruit flesh (Psidium guajava L.) as the test material. Phytochemical analysis and lip balm formulations were prepared at concentrations of 2.5%, 5%, 7.5%, 10%, along with a blank control. Commercially available products were used as a comparison. The physical quality evaluation of the formulations included tests for homogeneity, pH, melting point, stability, preference, and effectiveness on the lip skin using a moisture checker device. Results: the ethanolic extract of guava fruit flesh (Psidium guajava L.) can be formulated into a lip balm. The pH of the lip balm formulations ranged from 6.0 to 6.2 immediately after preparation and from 5.8 to 6.1 after 12 weeks of storage. The melting point of the formulations was between 58-62°C. The lip balm with a concentration of 7.5% was the most preferred in the preference test. The formulations remained stable in terms of odor, color, and shape over a 12-week storage period. The lip balm with a 10% concentration provided the best moisturizing effect on the lips, achieving a 23.1% improvement, while the commercial comparison product had an average recovery rate of 26.1%, falling under the